Influence of floodplains and groundwater dynamics on the present-day climate simulated by the CNRM climate model - B. Decharme; J. Colin (Earth System Dynamics)
The climate impacts of floodwater stored over large inundated areas and groundwater stored in large unconfined aquifers at the global scale are not yet well documented, despite their potential to affect the atmosphere through contributions to land surface evapotranspiration fluxes. To address these gaps in knowledge, the present study aims to assess the potential role of these processes in present-day climate using the CNRM-CM6-1 global climate model, the physical core of the Earth system model (ESM) used by the French National Center for Meteorological Research (CNRM) for climate projections. This model includes a dynamic river flooding scheme and a groundwater scheme, accounting for the world's 218 largest unconfined aquifer basins. The study consists of four experiments, each with five ensemble members driven by observed monthly sea surface temperature and sea ice cover for the 1980–2014 period. The experiments include configuration variations where both groundwater and floodplain processes were activated or deactivated and configurations where each process was individually activated. The various forcings used in CNRM-CM6-1 adhere to the CMIP6 recommendations. The false detection rate (FDR) test is employed to assess the significance of field differences. The simulated hydrological cycle is improved by representing floodplains and groundwater, thanks to an increased hydrological memory which allows us to better capture the seasonal cycle of the terrestrial water storage and river discharge. Additionally, the inclusion of groundwater and floodplains reduces precipitation and 2 m air temperature biases at the regional scale. Overall, the study highlights the importance of incorporating groundwater and floodplain processes into ESMs to improve the understanding of land surface–atmosphere interactions and the accuracy of climate simulations.